Chapter Prima dei Tuchini. Fedeltà di parte e comunità nelle valli del Canavese (Piemonte, secolo XIV) - Gravela, Marta (Reti Medievali E-Book, 2021)
Famous for the late 14th-century revolt known as Tuchinaggio, the Canavese area, in north-western Piedmont, provides significant information concerning the relationship between lords and subjects in a longer time span. By analysing a wide range of sources (pastoral visitations, chronicles, court and notarial records, statutes), the essay examines the domini-homines dialectic in the first half of the 14th century: in the Canavese Alpine valleys various degrees of institutional consolidation of communities can be outlined, identifying a process of growth common to communities in the entire Alpine Arc.